A Case of Oral-Vancomycin-Induced Rash in a Patient with Acute Kidney Injury - Milena Cardozo; Angadbir S. Parmar; Libardo Rueda Prada; Fnu Shweta (Infectious Disease Reports, 2023)
Clostridioides difficile infection (CDI) is one of the most common hospital-acquired infections. Its incidence has increased during the last decade in the community among individuals with no previous risk factors; however, morbidity and mortality are still considered high in elderly patients. Oral Vancomycin and Fidaxomicin are the first lines of treatment for CDI. The systemic bioavailability of oral Vancomycin is thought to be undetectable due to its poor absorption in the gastrointestinal tract; therefore, routine monitoring is not warranted. Only 12 case reports were found in the literature that described adverse reactions associated with oral Vancomycin and its related risk factors. We present a case of a 66-year-old gentleman with severe CDI and acute renal failure who was started on oral Vancomycin upon admission. On day five of treatment, he developed leukocytosis associated with neutrophilia, eosinophilia, and atypical lymphocytes, with no evidence of active infection. Three days later, he developed a pruritic maculopapular rash in more than 50% of his body surface area. Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) was ruled out since the patient only had three inclusion criteria for this diagnosis. No clear inciting agent was found. Oral Vancomycin was stopped and supportive treatment was supplied for a presumed Vancomycin-induced allergic reaction. The patient had an excellent response, with complete resolution of the rash and leukocytosis in less than 48 h. By reporting this case, we want to raise awareness among clinicians to remember that, albeit rare, oral Vancomycin can be the cause of adverse drug reactions in patients with severe illnesses.